Αντιλήψεις και συμπεριφορές του προσωπικού για την ασφάλεια των πασχόντων - Αθανάση, Αρτέμης (Τμήμα Νοσηλευτικής, Σχολή Επιστημών Υγείας, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2011)
Background: The safety of patients is one dimension of quality, which in recent years is being investigated in the health field and is of growing concern and research. This concern is exacerbated because the modern Health Systems are characterized by increased complexity resulting in increased bureaucracy and administrative cost control procedures. The complexity is aggravated health systems creates a multilayered mechanism at each level which always lurks the danger of error. Aim: The purpose of this work was to investigate (review) to focus on the perception and attitudes that have the health personnel in the operation of the hospital where they work and the impact it has on the safety of patients. Sample and method: For this purpose, we investigated the Greek-speaking and foreign language literature in international database PUBMED, CINAHL, EMBASE, and IATROTEK Eurobarometer surveys for the last five years. In addition to our source was Greek and Documentation Centre (File dissertations) with key words patient safety, staff perceptions, medical errors, safety attitudes, staff practices. Results: Through the search of the literature revealed that there are several systems of questionnaires that seek to assess the safety culture of the staff of hospitals. The most widely used tool is the method SAQ for which there is an extensive bibliography. The data from such surveys show that workers often feel that there is a need to improve the quality of service. Also, workers have a negative opinion climate that is formed at the hospital in response to errors. But because of our human nature that error is inevitable and will therefore need to create safeguards so that such errors be prevented and have no impact on patients without any impairment of wrong. To obtain a safety culture but ill staff should feel comfortable discussing the circumstances where the patient's safety was threatened both by colleagues and superiors. It should also strengthen the organization of seminars and courses in safety and maintain a history of errors, it is possible to review them and acquisition experience. Conclusion: There is an obvious need to recognize the importance of safety culture and the importance of the opinions of health professionals on security issues as they are direct and primary care providers.
Keywords: Patient safety; Medical errors; Nurse’s Role